1950
DOI: 10.3181/00379727-74-18005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Phagocytic Action of Leucocytes by Mumps and Influenza Viruses

Abstract: 320 0 1 ' I I I 3 ? 14 23 31 OAYS AFTER INlECnONS F I G . 3. Potentiation of a commercial aqueous testosteroae suspension by aluminum phosphate. Seminal vesicle response of immature rats to a single intramuscular injection.slower release from the depot site, it follows that a depot of micro-crystalline testosterone, subcutaneously or intramuscularly, should be ideal for slow absorption. As yet, there is no experimental demonstration of the mechanism by which aqueous A1P04 suspmsion of testosterone elicits a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

1958
1958
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 0 publications
3
15
0
1
Order By: Relevance
“…Thermic inactivation of Coxsackie viruses was found to de prive them of their ability to inhibit the phagocytic activity of leukocytes. Similar results were obtained with inactivated influ enza and mumps viruses (13). On the other hand, thermic inactiv ation of bacteriophages (10) and of vaccinia virus (14) did not suppress their action on leukocytes.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Thermic inactivation of Coxsackie viruses was found to de prive them of their ability to inhibit the phagocytic activity of leukocytes. Similar results were obtained with inactivated influ enza and mumps viruses (13). On the other hand, thermic inactiv ation of bacteriophages (10) and of vaccinia virus (14) did not suppress their action on leukocytes.…”
Section: Resultssupporting
confidence: 74%
“…It was observed that in experiments which resulted in complete inhibition the cells shrank to half their original diam eter, the structure of the nuclei became denser and they stained more intensly. It is noteworthy that similar morphological changes were reported by Merchant and Morgan (13) as well as by Kan toch, Skurski and Wieczorek (10). Merchant and Morgan found that influenza and mumps viruses decreased the phagocytic activ ity for bacteria by 20-30 per cent and simultaneously diminished the diameter of leukocytes.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The inhibitory effect on the antibacterial activity of phagocytic cells by virus infection has been described earlier (7,19). These in vitro studies suggest a direct antiphagocytic action of the virus on the leukocytes; however, the nature of the in vivo effects of virus infection on alveolar macrophages remain to be conclusively demonstrated.…”
Section: Discussionmentioning
confidence: 80%
“…Coxsackie virus, like other viruses, possesses the ability to inhibit the phagocytic activity of leukocytes (5,8,9,12). The degree of inhibition depends on the concentration of the viral pre paration used and on the duration of its action on the leukocytic cells.…”
Section: By M Karttoch and Anna Dubowska-inglotmentioning
confidence: 99%